2007
DOI: 10.1111/j.1439-0418.2007.01162.x
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodic influence on the body mass of bumblebee, Bombus terrestris and its copulation duration

Abstract: The body mass of Bombus terrestris individuals is an important trait for their behavioural performance and colony organization. In this study, colonies were reared under four different photoperiodic regimes, viz. 0 : 24, 8 : 16, 16 : 8 and 24 : 0 h light : darkness (L : D) at 28°C and 50% relative humidity. The changes in body mass were observed at the stages of larvae, pupae and on the day of adult eclosion. Both the wet and dry mass of sexuals gradually decreased with increasing day length. The relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
(41 reference statements)
1
11
0
Order By: Relevance
“…Similarly, Amin et al (2007) found a positive correlation between male mating number and copulation duration in B. terrestris . According to Brown and Bear (2005), possible reasons for this relationship might be that males invest more in mateguarding behavior with each copulation or that it takes longer to transfer sperm and mating plug material with each copulation.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Similarly, Amin et al (2007) found a positive correlation between male mating number and copulation duration in B. terrestris . According to Brown and Bear (2005), possible reasons for this relationship might be that males invest more in mateguarding behavior with each copulation or that it takes longer to transfer sperm and mating plug material with each copulation.…”
Section: Discussionmentioning
confidence: 75%
“…We also found that heavy males tended to remate more often, and copulate for less time, compared with lighter males. Similarly, Amin et al (2007) suggested that copulation duration was negatively correlated with male body mass, but positively with queen body mass. Male body mass was a significant predictor of the speed of mating initiation and copulation duration, with large males mating more quickly (Amin et al 2012).…”
Section: Male Remating In Bombus Terrestrismentioning
confidence: 99%
See 1 more Smart Citation
“…IT span is empirically related to dry body mass, IT span  = 0.77(dry weight) 0.405 ( R 2  = 0.96; mass in mg and IT in mm, [38]), so that body mass can be estimated from IT span data. We approximated the live weight of the bumblebee individuals by using the calculated dry weight and the live:dry weight ratios as reported in the literature [39].…”
Section: Methodsmentioning
confidence: 99%
“…An assumption of our calculation of queens' inclusive fitness, which incorporates fitness returns from both a queen's own sons and her workers' sons (queen's grandsons), is that queen-and worker-produced males do not differ in intrinsic quality. Given that male mass in B. terrestris influences male mating success (Duchateau & Marië n, 1995;Amin et al, 2007), we tested this assumption by measuring the masses of queen-and worker-produced males. In Hymenopteran societies, life-history strategy is potentially a function of the evolutionary interests of more than one party.…”
Section: Introductionmentioning
confidence: 99%